Dampak Konsumsi Makanan Berpengawet terhadap Kesehatan Masyarakat dan Strategi Penguatan Pengawasan Pangan di Indonesia - Maximilian Edward Tjang; Timothy Arthur Harrison; Fanny Indarto (Lembaga Pengembangan Kinerja Dosen, 2026)
Public health is a crucial aspect of national development and is influenced by dietary consumption patterns. In Indonesia, the consumption of preserved foods has increased alongside lifestyle changes, economic conditions, and access to processed and packaged foods. Although preservatives function to extend shelf life, their improper use particularly hazardous substances such as formaldehyde, borax, and rhodamine B can have adverse health effects. This study aims to identify the factors contributing to high preserved food consumption, analyze their impact on public health, and examine weaknesses in Indonesia’s food monitoring system. The research employs a qualitative method through a literature review of scientific articles, reference books, and official reports from the National Agency of Drug and Food Control and the Ministry of Health. The findings indicate that preserved food consumption is influenced by a preference for convenience, economic constraints, and limited public knowledge of nutrition and food safety. Health impacts include digestive disorders, decreased immunity, impaired organ function, and an increased risk of chronic diseases. In addition, limited resources and weak law enforcement contribute to suboptimal food supervision. Therefore, strengthening regulatory oversight, enhancing public education, and promoting cross-sector collaboration are necessary to achieve a safe and healthy food system.